2016
DOI: 10.1093/ejo/cjv097
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilver coated orthodontic brackets:in vivoantibacterial properties and ion release

Abstract: It is suggested that nanosilver coated orthodontic brackets, as an antibacterial agent without patient compliance, could be helpful for the prevention of white spot lesions during fixed orthodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 46 publications
2
62
0
Order By: Relevance
“…Other study evaluated, through an in vivo experimental design, the antimicrobial activity on S. mutans bacteria and the ion release capacity of nanosilver-coated orthodontic brackets; these authors concluded that AgNP-coated brackets could significantly help to decrease the presence of spot lesions during fixed orthodontic treatments, even may have a potential solution for systemic compromised patients such as immune deficiency, diabetics, and subacute bacterial endocarditis. [21]. Our results agree with these results indicating that both sizes of AgNP samples have significant ability to inhibit the adherence capacity of S. mutans bacteria on surfaces of elastomeric modules and orthodontic brackets, even for these orthodontic brackets and elastomeric modules crisscrossed (p < 0 05).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other study evaluated, through an in vivo experimental design, the antimicrobial activity on S. mutans bacteria and the ion release capacity of nanosilver-coated orthodontic brackets; these authors concluded that AgNP-coated brackets could significantly help to decrease the presence of spot lesions during fixed orthodontic treatments, even may have a potential solution for systemic compromised patients such as immune deficiency, diabetics, and subacute bacterial endocarditis. [21]. Our results agree with these results indicating that both sizes of AgNP samples have significant ability to inhibit the adherence capacity of S. mutans bacteria on surfaces of elastomeric modules and orthodontic brackets, even for these orthodontic brackets and elastomeric modules crisscrossed (p < 0 05).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, silver nanoparticles (AgNPs) have been shown to be materials with excellent antimicrobial properties in a wide variety of microorganisms [6,[16][17][18][19]. In the orthodontic field, studies have incorporated AgNPs (17 nm) into orthodontic elastomeric modules, orthodontic brackets and wires, and others, against a wide variety of bacterial species concluding that these orthodontic appliances with AgNPs could potentially combat the dental biofilm decreasing the incidence of dental enamel demineralization during and after the orthodontic treatments [20][21][22][23]. However, there is no information that has evaluated the antimicrobial effect and antiadherence activity of AgNPs against S. mutans bacteria on orthodontic bracket surfaces and its relationship with the presence of the elastomeric modules as well as different types of metallic orthodontic wires and the involved factors in the adherence of these bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of our clinical observations, differences considered to be symptoms of argyria were observed in none of the animals. A previous study showed that nanosilver-coated orthodontic brackets prevent caries formation via its antibacterial properties [16]. The present study suggests, with the support of other previous studies, that nanosilver-coated orthodontic brackets have no disadvantage in terms of biocompatibility, and also it can be useful during fixed orthodontic treatment.…”
Section: Discussionsupporting
confidence: 87%
“…The nanoparticles show efficient antimicrobial properties due to their extremely large surface area, which provides better contact with microorganisms. Researchers reported that orthodontic brackets coated with nanoparticles or combining dental material with nanoparticles show antibacterial and anti-adhesive properties against normal oral pathogenic bacteria [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…These are including certain NPs, such as nanofillers, silver, TiO 2 , SiO 2 , hydroxyapatite, fluorapatite, fluorohydroxyapatite, into orthodontic bonding materials or acrylic resins and coating surfaces of brackets and bands. Information of using nanotechnology is lacking; thus, further investigation to assess possible toxicity related to the NP sizes is required [106][107][108].…”
Section: Increasing Tooth Resistancementioning
confidence: 99%